Orders for Security for Costs and International Arbitrations in Singapore - HSU, Locknie (Institutional Knowledge at Singapore Management University, 2000)
Cases concerning applications for security for costs under 1994 Act and important issues raised, including need for clear guidelines on how and when court should order stay of proceedings in international arbitration.